Multilingualism in Immigrant Journalism by Ilya Surguchev - T. S. Shevchenko (Научный диалог)
The article focuses on the role of foreign language vocabulary in Ilya Surguchev’s journalism (based on the cycle of “The Paris diary,” 1940-1945). The research urgency is caused by the fact that the language of I. Surguchev’s texts, as the emigrant press language in 1940-ies is still unknown. The factors that influenced the formation of the multi-layered structure of I. Surguchev’s language personality are revealed. The features of foreign words, free and bound collocations, idioms, proverbs, quotations in foreign languages: Latin, French, Italian, English, Ukrainian, Chinese etc., functioning in I. Surguchev’s texts, are considered. Classification of foreign language vocabulary, among which there are regular borrowings (internationalisms, exoticism, proper names, quasi- borrowings, marked borrowing, etc.) and occasional ones (the most striking features of idiostyle of the writer). Etymological information about words in foreign language is given. Attention is paid to the features of I. Surguchev’s translation of foreign-language material into Russian. On the metalinguistic level, I. Surguchev’s evaluation of “foreign word” by a phonosematic criterion is revealed. It is concluded that I. Surguchev’s journalism is characterized by multiculturalism, multilingualism, polyphonism, intertextuality, stylistic convergence. Special attention is paid to the I. Surguchev commitment to the preservation of the values of Russian culture.